2014
DOI: 10.1111/cas.12472
|View full text |Cite
|
Sign up to set email alerts
|

Alternative polyadenylation is associated with lower expression of PABPN1 and poor prognosis in non‐small cell lung cancer

Abstract: Alternative polyadenylation (APA), which induces shortening of the 3′UTR, is emerging as an important phenomenon in gene regulation. APA is involved in development, cancer and cell proliferation. APA may lead to disruption of microRNA-mediated gene silencing in cancer cells via detachment of microRNA binding sites. We studied the correlation between the APA profile and the tumor aggressiveness in cases of lung cancer. We selected the top 10 genes showing significant 3′UTR shortening in lung cancer, using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Calcium is one of the key factors in stabilizing the cell cycle, and CALB1 can interfere with the resorption and homeostatic processes of calcium, ultimately regulating cell apoptosis . In addition, studies have shown that CALB1 can play a role in early tumor diagnosis and recurrence prediction . TOP2A, or topoisomerase IIa, has been shown to be involved in proliferation, apoptosis, and tumor resistance mechanisms in various studies .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is one of the key factors in stabilizing the cell cycle, and CALB1 can interfere with the resorption and homeostatic processes of calcium, ultimately regulating cell apoptosis . In addition, studies have shown that CALB1 can play a role in early tumor diagnosis and recurrence prediction . TOP2A, or topoisomerase IIa, has been shown to be involved in proliferation, apoptosis, and tumor resistance mechanisms in various studies .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this hypothesis, known protein interaction sites, such as regions needed for interaction with SKIP (residues 2–145), stimulation of poly(A) polymerase alpha (PAPOLA, residues 119–147) and coiled-coil-based interaction (residues 115–151), are all located within the N-terminal IDPR. Being the only non-transcription factor with the pathogenic poly-Ala tract, PABP2/PABPN1 does not form an exception from the multipathogenicity rule, being associated with oculopharyngeal muscular dystrophy via the expansion mutations in its poly-Ala tract [ 269 ] and also being involved in metastatic duodenal cancer [ 270 ] and non-small cell lung cancer [ 271 ].…”
Section: Intrinsic Disorder In Proteins Associated With Pathologicmentioning
confidence: 99%
“…The expression levels of the polyadenylation complex subunits can also be deregulated in solid cancer cells. For example, PABPN1 and CPSF4 are, respectively, downregulated [123] and upregulated [124] in lung tumors. devoted to the control of the different phases of the transcription cycle.…”
Section: Box 2 Transcription Termination and Hematopoietic Malignanciesmentioning
confidence: 99%